Separate and Concentrate: Accounting for Patient Complexity in General Hospitals - Kuntz, Ludwig; Scholtes, Stefan; Sülz, Sandra (Management Science, 2019)
Scholars have recently suggested the reorganization of general hospitals into organizationally separate divisions for routine and non-routine services to overcome operational misalignments between the two types of services. We provide empirical evidence for this proposal from a quality perspective, using over 250,000 patient discharge records from 60 German hospitals across 39 high-mortality disease segments, and focusing on in-hospital mortality as outcome. Disentangling the effects of high, absolute, and relative hospital volumes in a disease group, our analysis suggests that routine and complex patients would benefit from a hospital organization with a multi-specialty hub for emergency and non-routine elective services at its core, complemented by organizationally separate disease-focused hospitals-within-hospitals for routine services. We also provide evidence that the hub hospital can further improve service quality for complex patients by adopting a disease-based rather than medical specialty-based departmental routing strategy for newly arriving patients. A counterfactual analysis, based on a simultaneous equations probit model that simultaneously controls for endogeneity of volume, focus, and routing strategy, suggests that the proposed reorganization could have reduced mortality in the sample by 13.43% (95% CI [6.87%; 18.95%]) for routine patients and by 11.67% (95% CI [6.13%; 16.86%]) for the most complex patients. The supplementary material is available at https://doi.org/10.1287/mnsc.2018.3064 . This paper was accepted by Serguei Netessine, operations management.